KEANEKARAGAMAN JENIS JAMUR MIKORIZA ARBUSKULA PADA TANAMAN JABON (Anthocephalus spp) - hanuddin, Bur (Universitas Tanjungpura, 2012)
Anthocephalus spp is one type of wood is fast growing and straight-trunked. The community is now much interested in developing Anthocephalus spp plantations as peoples because the selling price is expensive. The study of mycorrhizal fungi species diversity in Anthocephalus spp plants aim to get the types of mycorrhizal and mycorrhizal density in Anthocephalus spp stands. This research uses descriptive method by taking soil samples in the rhizosfere some level Anthocephalus spp tree poles and trees. At every level of growth Anthocephalus spp each taken 3 plants. The results obtained in the Anthocephalus spp stands found that seven morphotife. Spores of arbuscular mycorrhizal fungi are 2 morphotife spores is Gigaspora genera, 4 morphotife spores is Glomus and one Acaulaspora genera. Spore density of arbuscular mycorrhizal fungi on Anthocephalus spp stands at the pole with a density of spores 3-77 with a mean of 42 spores and spore density tree level 4-52 with a mean of 26 spores. Key word: Anthocephalus spp, mycorrhizal, Ultisol, Organosol, and Alluvial